A Study on Halal Cosmetic Awareness Among Malaysian Cosmetics Manufacturers - Mustafar, Mastora; Ismail, Risyawati Mohamed; Othman, Siti Norezam; Abdullah, Rohani (International Journal of Supply Chain Management, 2018)
Halal certification and acceptance of Halal products had been widespread in the hospitality, food, packaging, banking and finance industries. In the food sector, Halal consciousness is especially high among consumers as well as the governments. However, the demand for Halal cosmetics and beauty products is not as strong. With increasing consumer awareness and a willingness to pay for quality products, the scenario is changing, thereby transforming the cosmetics and personal care industry into a potential sunrise segment for the region. Therefore, the purpose of this study was to conduct an exploratory investigation on the awareness of halal certification process among cosmetics manufacturers. A sample random t-test and descriptive analysis was used upon among cosmetics entrepreneurs in Malaysia. The data was selected based on simple random sampling from MIHAS Book directory which has listed the companies involved in the 13th edition Malaysia International Halal Showcase in Kuala Lumpur. Findings from this study indicated that Malaysia cosmetic manufacturers are well aware of the halal certification process and competent in obtaining halal certification. Future research should look into studying manufacturers which have yet to obtain halal certification in order to full comprehend this issue in depth